2010
DOI: 10.1002/jez.b.21386
|View full text |Cite
|
Sign up to set email alerts
|

New insights on ctenophore neural anatomy: Immunofluorescence study in Pleurobrachia pileus (Müller, 1776)

Abstract: Ctenophores are non-bilaterian animals sharing with cnidarians and bilaterians the presence of sensory receptors, nerve cells, and synapses, absent in placozoans and sponges. Although recent immunofluorescence studies have renewed our knowledge of cnidarian neuro-anatomy, ctenophores have been much less investigated despite their importance to understanding the origin and early evolution of the nervous system. In this study, the neuro-anatomy of the ctenophore Pleurobrachia pileus (Müller, 1776) was explored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
135
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(159 citation statements)
references
References 60 publications
22
135
2
Order By: Relevance
“…FMRFamide-like and vasopressin-like immunereactivities were reported in some Pleurobrachia neurons (Grimmelikhuijzen, 1983;Jager et al, 2011), but none of these neuropeptide classes were found in the recent genomic studies . Cholinergic and monoaminergic control of bioluminescent flashes were proposed for Mnemiopsis (Anctil, 1985) but neither effector neurons nor specific transmitter synthetic enzymes were identified.…”
Section: Tripartite Synapses In Ctenophoresmentioning
confidence: 97%
“…FMRFamide-like and vasopressin-like immunereactivities were reported in some Pleurobrachia neurons (Grimmelikhuijzen, 1983;Jager et al, 2011), but none of these neuropeptide classes were found in the recent genomic studies . Cholinergic and monoaminergic control of bioluminescent flashes were proposed for Mnemiopsis (Anctil, 1985) but neither effector neurons nor specific transmitter synthetic enzymes were identified.…”
Section: Tripartite Synapses In Ctenophoresmentioning
confidence: 97%
“…However, we have to recognize that those genes could also have been co-opted several times in evolution (in toto or a fraction of them; see, for instance, [83]) or used for the general patterning of the neuroepithelia, instead of being devoted to the specification of concrete neural areas/ structures [84 -86]. The alternative hypothesis is the multiple origin of centralized NSs, which states that they have evolved, independently, more than once [84,85,101,102]. The hypothesis relies on the observation that there is a 'patchy' rstb.royalsocietypublishing.org Phil.…”
Section: Independent Events In Nervous System Centralization Across Mmentioning
confidence: 99%
“…N. vectensis constitutes an ectodermal and endodermal nerve net making it a simple and diffuse nervous system that runs throughout the animal's body (Marlow et al, 2009;Nakanishi et al, 2012). Also, recently, the ctenophore (M. leidyi) genome has been sequenced and the organism also possesses a peripheral subepithelial nerve net, neurons and nerves associated with the tentacles (Jager et al, 2011;Richter and King, 2013;Ryan et al, 2013). Here, we analyse the large expansions of GPCRs, and present the evidence accumulated so far for the presence of neurotransmitters and their roles in early metazoans.…”
mentioning
confidence: 99%